Bimetallic Bi–Sn micro-/nanospheres@cellulose nanocrystal derived carbon aerogel composite anode for high-performance Mg-ion batteries. (April 2023) - Liu, Junjie; Cheng, Miao; Liu, Qianqian; Wang, Ruirui; Wei, Yinghui; Ma, Wujun; Hu, Jing; Wei, Tao; Ling, Yun; Liu, Bo; Chen, Muzi; Li, Wanfei
Abstract: Magnesium-ion batteries (MIBs) have recently received widespread attention for energy storage. Nevertheless, the development of suitable anode materials remains significant challenges. Herein, a novel bimetallic Bi–Sn micro-/nanospheres homogenously embedded in cellulose nanocrystal derived carbon aerogel (CNC-CA@Bi–Sn) composite was constructed through a facile ion-induced gelation and in-situ thermal reduction processes. As an anode for MIBs, the CNC-CA@Bi–Sn electrode delivered high reversible specific capacity of 334 mAh g −1 after 100 cycles at 100 mA g −1, superior rate performance and long cycling lifespan with a reversible capacity of 187 mAh g −1 (ultralow capacity fade rate of 0.099% per cycle) at high current density of 1000 mA g −1 for 500 cycles. The excellent electrochemical performance should be attributed to the synergetic effects of unique three-dimensional (3D) nanoporous structure, dual phase microstructure and rich phase boundaries, biphase-based and carbon buffering matrices, which could effectively accommodate the large volume changes during the demagnesiation/magnesiation processes, significantly shorten diffusion lengths and improve the diffusion kinetics of Mg 2+ . This work provided a promising strategy for the design and synthesis of Bi–Sn biphasic material coupling with 3D carbon aerogel, which could be extended to other novel electrodes for high-performance MIBs. Graphical abstract: Image 1 Highlights: Bi–Sn micro-/nanospheres embedded in CNC derived CA was prepared as anode for MIBs. CNC-CA@Bi–Sn delivered high reversible capacity and superior rate capability. CNC-CA@Bi–Sn showed remarkable cycling stability at 1000 mA g −1 for 500 cycles. Bimetallic Bi–Sn and CA matrix synergistically enhanced electrochemical performance.